Influência da função pulmonar na resposta vascular de indivíduos com COVID longa - Carvalho, Lêda Leonôr Mendonça (Universidade Federal de São Carlos, 2025)
“Long COVID” is a term commonly used to describe the presence of symptoms, even weeks or months after SARS-CoV-2 infection. It can also be called “post-COVID syndrome”, and it can be continuous or recurrent and remitting in nature. It is characterized by the persistence of one or more symptoms of acute COVID or the appearance of new symptoms. Knowing all the implications that COVID-19 survivors face with respiratory sequelae, the question arises in the literature as to how lung function can influence the vascular response of these patients. Objective: to evaluate the influence of lung function on the vascular response of patients with long COVID. Methods: This is an observational and cross-sectional study. Participants were evaluated in the morning in only one visit and during it the evaluation form was answered and the Post-COVID-19 Functional Status Scale (PCFS) was applied. In addition, the evaluation of flow-mediated vasodilation in the brachial artery and the assessment of complete lung function were performed through whole body plethysmography. The simple linear regression model was used to determine the association between the study variables. A significance level of 5% (p<0.05) was adopted in all analyses. Results: Forty-two volunteers were initially recruited for this research, 10 had to be excluded. A total of 32 participants were included, of which 19 were women and the remainder were men. The mean age was 55.8 ± 8.6 years, with a mean weight of 88.96 ± 21.66 kg. The participants had an average time of 32.25 months since the acute episode. Pearson's correlation analysis revealed a significantly positive difference between the vascular function parameter, basal diameter, and lung function variables. Conclusion: The lung function influences the vascular response of patients with long COVID. More than two years after recovery from COVID-19 infection, we observed a high burden of persistent symptoms and changes in endothelial function, which have important implications for individuals when we talk about cardiovascular health.
Influence of lung function nn the vascular response of individuals with long COVID
Keywords: Síndrome de COVID-19 pós-aguda; COVID longa; Testes de função respiratória; Endotélio vascular; Post-Acute COVID-19 syndrome; Long COVID; Respiratory function tests; Vascular endothelium; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL